Land use problems and possible solutions - Vlasenko, A. O. (ТДАТУ, 2020)
Land resources are not just a factor of production, but the main component that provides the spatial and territorial prerequisites for the use of the resource base for the economic and social development, as well as their reproduction. That is why there is a need to create an effective mechanism for improving land policy, which will increase socio-economic and environmental land use efficiency in the world.
Keywords: modern development of the agrarian economy; land resources; rational land use is